2003
DOI: 10.1016/s0042-6822(02)00035-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple amino acid residues confer temperature sensitivity to human influenza virus vaccine strains (flumist) derived from cold-adapted a/ann arbor/6/60

Abstract: FluMist influenza A vaccine strains contain the PB1, PB2, PA, NP, M, and NS gene segments of ca A/AA/6/60, the master donor virus-A strain. These gene segments impart the characteristic cold-adapted (ca), attenuated (att), and temperature-sensitive (ts) phenotypes to the vaccine strains. A plasmid-based reverse genetics system was used to create a series of recombinant hybrids between the isogenic non-ts wt A/Ann Arbor/6/60 and MDV-A strains to characterize the genetic basis of the ts phenotype, a critical, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(162 citation statements)
references
References 19 publications
4
157
1
Order By: Relevance
“…This feature of influenza virus pathogenesis was also used to reduce the virulence of human influenza strains and produce a safe live influenza vaccine. The currently licensed, live-attenuated, cold-adapted influenza vaccine uses a master donor virus that is adapted for replication in primary chicken kidney cells at low temperature, producing a virus capable of only limited nonpathogenic infection of humans and limited transmission among humans (51). Ferrets are more susceptible to infection with human influenza isolates than mice and develop rhinitis that is similar to that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of influenza virus pathogenesis was also used to reduce the virulence of human influenza strains and produce a safe live influenza vaccine. The currently licensed, live-attenuated, cold-adapted influenza vaccine uses a master donor virus that is adapted for replication in primary chicken kidney cells at low temperature, producing a virus capable of only limited nonpathogenic infection of humans and limited transmission among humans (51). Ferrets are more susceptible to infection with human influenza isolates than mice and develop rhinitis that is similar to that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the attenuated live vaccines, the virus is cold adapted, e.g., attenuated by serial passage at low temperature, resulting in a live virus that can not cause significant illness in human. 1 In addition to the whole virus trivalent vaccine, subunit vaccines that are based on viral envelope proteins (HA and NA) are also approved for human use. It has been shown that such vaccines are highly immunogenic and well tolerated in children, young adults, and among the elderly.…”
Section: Background-available Influenza Vaccines Limitations and Thementioning
confidence: 99%
“…Two types of influenza vaccines are currently available, the trivalent or quadrivalent inactivated influenza vaccine (TIV/QIV), which is given intramuscularly, and the live attenuated influenza vaccine (LAIV), which is administered intranasally. LAIV have been engineered by reverse genetics using the HA and NA genes from circulating viruses and an attenuated, temperature-sensitive, cold-adapted backbone, which prevents replication of the virus at temperatures above 33°C, thus limiting virus infection to the upper airways (8,9). Following inhalation of LAIV, the palatine tonsils, the NALT equivalent in humans, is the site where the humoral immune response is initiated (15).…”
Section: Discussionmentioning
confidence: 99%
“…We next assessed the anatomical location of CTL priming following immunization with the LAIV vaccine, which is engineered to preferentially replicate in the lower temperatures of the upper airways (7)(8)(9) and monitored the endogenous CD8 + T-cell response directed against influenza viral proteins. The CD8 + T-cell response following influenza virus infection of C57BL/6 mice is predominately directed against two viral proteins, the nucleoprotein (NP) and acid polymerase (PA) and can be monitored using H-2D b tetramers loaded with the PA 224 and NP 366 epitopes.…”
Section: Significancementioning
confidence: 99%